Legislating Interprofessional Regulatory Collaboration in Nova Scotia - William Lahey (McMaster University Library Press, 2013)
To shift health professions regulation from traditional to 'collaborative' self-regulation, Nova Scotia has adopted legislation which will: make all self-regulating health professions members of the Regulated Health Professions Network; mandate the Network to facilitate voluntary collaboration among its members; and enable regulators to work together on investigations of patient complaints, to adjust scopes of practice on an ongoing basis and to adjudicate appeals of unsuccessful applicants for registration. The goals are to give health professions regulation the capacity to enable and support the functioning of interprofessional teams. The legislation was adopted primarily for two reasons: collaborative development and unanimous support by all of the province's self-regulating professions; and alignment with the government's health care reform agenda and its emphasis on collaborative team-based care. Contrary to the approach of several other provinces, the legislation will enable but not require regulators to collaborate on the premise that consensual collaboration is more likely to happen, to be meaningful and to yield tangible benefits. Support for this approach can be taken from the impressive collaborative work on which the legislation is based. Evaluation will be critical, and the five-year review required by the legislation will give Nova Scotia the opportunity to test not only the legislation but the ideas on which it is based. The extent of the legislation's reliance on voluntary process will prove to be either its greatest strength or its greatest weakness. Afin de faire passer la régulation des professions de santé du modèle traditionnel à un modèle d'auto-régulation « collaborative », la Nouvelle-Écosse a adopté une législation aux fins suivantes : créer un Réseau des Professions de Santé Régulées incluant toutes les professions auto-régulées; mandater le Réseau pour faciliter la collaboration volontaire entre ses membres; et permettre aux régulateurs de travailler ensemble sur les enquêtes sur les plaintes des patients, sur l'ajustement dans le temps des champs de pratiques ainsi que sur les appels de candidats à l'enregistrement dont la candidature aurait été rejetée. L'objectif est de donner à la régulation des professions de santé la capacité d'encourager et de soutenir le fonctionnement d'équipes interprofessionnelles. Deux facteurs principaux ont rendu possible l'adoption de cette législation : son développement fut collaboratif et soutenu par toutes les professions auto-régulées de la Province; ensuite, elle s'alignait avec les projets de réforme de la santé du gouvernement et l'importance qu'ils donnent à la coopération au sein d'équipes soignantes. Contrairement à l'approche adoptée dans plusieurs autres provinces, la législation autorisera mais n'imposera pas aux régulateurs de collaborer, l'idée étant que la collaboration consensuelle a plus de chance de se produire réellement et de donner des résultats tangibles. Que l'approche rencontre l'approbation peut être démontré par l'impressionnante collaboration ayant travaillé à la préparation du texte de loi. L'évaluation sera une étape critique, et la revue à cinq ans inscrite dans la loi donnera à la Nouvelle-Écosse l'occasion de tester non seulement cette législation mais aussi les idées sur lesquelles elle repose. Le fait que la législation repose essentiellement sur l'engagement volontaire pourra être sa plus grande force ou sa plus grande faiblesse.